The Evaluation of Forage Silage Related Traits Between Maize and Hybrid Giant Napier (Pennisetum Hydridum) - Kexiang Yang; Angui Wang; Pengfei Liu; Xiangyang Guo; Jiaqi Shen; Yunfang Zhu; Xun Wu; Zehui Chen (Journal of Agronomy Research, 2022)
Selecting elite silage specific variety was important for modern animal husbandry development and agricultural production. In this paper, six forage quality related physiology traits were evaluated by using chemical detection method, the difference between maize silage and hybrid giant napier (pennisetumhydridum) were analyzed. Results showed that, maize showed better performance than that of hybrid giant napier, with average protein content of 8.54% VS 7.48%, starch content of 11.18% VS 7.90%, soluble sugar content of 4.09% VS 2.90%, and IVOMD of 35.23% VS 34.94%, respectively. No significant differences were found for NDF content and ADF content between maize and hybrid giant napier. In addition, QQ446 showed better performance than that of JY818, with higher IVOMD of 35.50% VS 34.95%, higher protein content of 8.60% VS 8.48%, higher starch content of 11.82% VS 10.53%, and lower ADF content of 32.86% VS 37.43%. These results proved that, QQ446 was the elite silage specific variety, it contained much more forage advantages, and could be widely used in future animal husbandry development and agricultural production.
Keywords: Forage quality